The plausibility of <c + a> dislocation slip on {-12-11} planes in Mg. (November 2018) - Zhang, Jiadong; Zhang, Yong; El-Awady, Jaafar A.; Tang, Yizhe
Abstract: Here, the slip behavior of < c + a > screw dislocations on first-order and second-order pyramidal planes in Mg are systematically investigated. Slip or/and cross-slip on six low Miller-Bravais-index planes, including two new {-12-11} planes that have hitherto not been considered possible, are all observed. This new slip system has a low Peierls stress and generalized stacking fault energy, suggesting that it might be an easy mode. The active cross-slip and new slip system provide new insight into the plasticity mechanisms of Mg. Graphical abstract: Unlabelled Image